Holographically recorded gratings on microlenses for a miniaturized spectrometer array - Traut, S.; Herzig, Hans-Peter (My University, 2000)
We report on the investigation of refractive microlens arrays with diffractive grating surfaces in the context of a microspectrometer array system. The elements fabricated combine the fairly large dimensions of the refractive microlens (990-µm diam, 60-µm height) with the submicron features of the diffraction grating (1-µm grating period) on one transmitting surface. The fabrication process of these elements was studied, as well as their performance with respect to resolution and stray-light suppression. The maximum resolution was 3 nm, and the stray-light suppression 25 dB. We present a concept for a system of miniaturized spectrometer arrays for chemical analysis.
Keywords: microspectrometer; hybrid element; spincoating; microlens array